'Laatste avond corpslustrum eind eerste studentencursus ('96/97)'. Eerste links zittend Adama van Scheltema - Schuitvlot, Nic., (1897)
'Laatste avond corpslustrum eind eerste studentencursus ('96/97)'. Eerste links zittend Adama van Scheltema.